Active modified atmosphere packaging, postharvest physiology, quality attributes and shelf life of minimally processed pomegranate arils (cv. Wonderful) - Banda, Kalenga (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2015.